Predictive ability of financial variables in changing economic circumstances - Kuosmanen, Petri; Rahko, Jaana; Vataja, Juuso (Elsevier, 2018)
We analyze three key financial variables, the term spread, real stock returns and the real short-term interest rate, and study which economic factors underlie changes in their predictive power for GDP growth in a large set of industrialized countries. Our results show that the enhanced predictive content of financial variables is connected to increased GDP and stock market volatility as well as turning points in business cycles. Periods with a zero lower bound of interest rates appear to reduce the predictive ability of stock markets. Moreover, we find qualified evidence that inflation persistence increases the predictive content of financial variables.
Keywords: forecasting; macroeconomy; short-term interest rates; stock market; term spread; fi=Taloustiede|en=Economics|